Knowledge of medical students about perioperative nutritional care in Bahia, Brazil: a transversal study - Rodrigo Fernandes Weyll Pimentel; Leonardo Castro Dantas Macêdo; Sérgio Diniz Gonçalves Queiroz Filho; Pedro Carlos Muniz de Figueiredo; Magno Conceição das Merces (Escola Bahiana de Medicina e Saúde Pública, 2021)
OBJECTIVE: Evaluate the medical students' knowledge about perioperative nutritional care. These students are from public and private academic institutions in the state of Bahia, Brazil. METHODS: This is a cross-sectional study to analyze medical students based on an online instrument regarding topics related to perioperative care. For data analysis, absolute and relative frequencies were calculated for categorical variables, and mean and standard deviation were calculated for continuous variables. Fisher's Exact Test and G Test were used to analyze the association. Results: 209 responses were obtained. Regarding the learning on nutritional preparation of the patient submitted to a surgery, 25 (64.9%) students of public institutions and 90 (52.3%) students of private ones reported not knowing or not having been exposed to such knowledge. Regarding the importance of addressing topics related to nutritional therapy (NT), 37 (100%) students from public institutions and 168 (97.7%) from private ones recognize the importance of spreading this knowledge. Unnecessary absolute preoperative fasting, shortening techniques of fasting and bronchoaspiration prevention and reintroduction time of a diet in the postoperative period are unknown to most of the population studied. CONCLUSION: Most students included in this study do not have satisfactory knowledge in NT and for preparing the surgical patient.